Increased Proportion of CD226+ B Cells Is Associated With the Disease Activity and Prognosis of Systemic Lupus Erythematosus - Nakano, Miki; Ayano, Masahiro; Kushimoto, Kazuo; Kawano, Shotaro; Higashioka, Kazuhiko; Inokuchi, Shoichiro; Mitoma, Hiroki; Kimoto, Yasutaka; Akahoshi, Mitsuteru; Ono, Nobuyuki; Arinobu, Yojiro; Akashi, Koichi; et al. (Frontiers in Immunology, 2021)
Background CD226, an activating receptor expressed on the surface of natural killer (NK) cells and T cells, is also seen on B cells and CD226 polymorphism is associated with systemic lupus erythematosus (SLE). Because the specific roles of CD226+ B cells in SLE are still unknown, we investigated the association of CD226+ B cells with SLE. Methods We measured CD226 expression on B cells and its subsets using flow cytometry in 48 SLE patients and 24 healthy controls (HCs). We assessed the relationships between CD226+ B cells and SLE Disease Activity Index 2000 (SLEDAI-2K), clinical manifestations, laboratory data, and prognosis after 12 months. Results The proportions of CD226+ cells in whole B cells and all its subsets were significantly higher in SLE patients than HCs. In SLE patients, the proportions of CD226+ B cells and CD226+ switched-memory (SM) B cells were significantly correlated with SLEDAI-2K scores and anti-dsDNA antibody titers, and negatively correlated with serum complement levels. Moreover, basal percentages of CD226+ B cells and CD226+ SM B cells were low in patients who were in Lupus Low Disease Activity State after 12 months. In patients with renal involvement, the proportion of CD226+ B cells increased. Additionally, the proportion of CD226+ B cells was higher in patients who were not in complete renal remission after 12 months. Conclusions Increased proportion of CD226+ B cells was associated with disease activity and prognosis of SLE. CD226+ B cells may be a useful biomarker for the management of SLE.